2020
DOI: 10.3389/fnhum.2020.00048
|View full text |Cite
|
Sign up to set email alerts
|

The Weakened Relationship Between Prestimulus Alpha Oscillations and Response Time in Older Adults With Mild Cognitive Impairment

Abstract: Background: Prestimulus alpha oscillations associated with preparatory attention have an impact on response time (RT). However, little is known about whether there is a deficit in the relationship between prestimulus alpha oscillations and RT in older adults with mild cognitive impairment (MCI). Method: We collected electroencephalography (EEG) data from 28 older adults with MCI and 28 demographically matched healthy controls (HCs) when they were performing an Eriksen flanker task. For each participant, single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 69 publications
2
8
0
Order By: Relevance
“…These results validate the reported improvements in cognitive skills found previously [62] using robust neuropsychological tests. Since coupled alpha-gamma activity is reduced in older adults with mild cognitive impairments resulting from memory loss [68], the improvements found in this person's working memory provides more evidence PATH training improves both coupled alpha-gamma and theta-gamma activity. For both people, improvements in cognitive skills were measured using a battery of standardized tests before and after 8 weeks of PATH neurotraining twice a week for 15-20 minutes, providing more rigorous evidence than available previously.…”
Section: Improving Visual Dorsal Stream Function Remediates Reading Fluency Attention Span and Memory Retentionmentioning
confidence: 85%
See 1 more Smart Citation
“…These results validate the reported improvements in cognitive skills found previously [62] using robust neuropsychological tests. Since coupled alpha-gamma activity is reduced in older adults with mild cognitive impairments resulting from memory loss [68], the improvements found in this person's working memory provides more evidence PATH training improves both coupled alpha-gamma and theta-gamma activity. For both people, improvements in cognitive skills were measured using a battery of standardized tests before and after 8 weeks of PATH neurotraining twice a week for 15-20 minutes, providing more rigorous evidence than available previously.…”
Section: Improving Visual Dorsal Stream Function Remediates Reading Fluency Attention Span and Memory Retentionmentioning
confidence: 85%
“…These results show cognitive transfer to untrained tasks. Since coupled alpha-gamma activity is reduced in older adults with mild cognitive impairments [68], these improvements in working memory provide more evidence PATH training improves coupled alpha-gamma activity Following PATH neurotraining, this older adult's quality of life improved remarkably. She reported "My memory, reading speed, ease of understanding, processing speed, ability to multitask, concentrate, and pay attention have improved remarkably in just a few months.…”
Section: Older Adult Improved In Reading Attention Processing Speed and Working Memorymentioning
confidence: 93%
“…The initial inertia relates directly to the brain activation needed to integrate sensory evidence. Petro et al (2019) and Chen et al (2020) have shown in human EEG studies that depending on the brain activity prior to stimulus presentation changed the speed of responses. More specifically, they showed that the more pre-activated the required sensory area, the faster the decision.…”
Section: Discussionmentioning
confidence: 99%
“…The limited previous MEG studies of selective attention in the context of HIV have found altered theta and alpha activity, with theta predicting neuropsychological outcomes and distinguishing cognitively impaired and unimpaired PWH [ 29 ]. Though no task-based MEG studies of selective attention in ADS exist, recent EEG studies have found alpha activity to be altered in ADS disorders during attentional processing and recent resting-state MEG studies in AD have found consistent links between low-frequency activity and attention and processing speed [ 27 , 28 , 30 , 31 ]. Given the limited work in this area, it is not surprising that no studies to date have directly examined the potentially shared and disease-specific aberrations in neural circuitry serving attention in those with HAND versus ADS.…”
Section: Introductionmentioning
confidence: 99%
“…Given these deficits, all participants completed an arrow-based Eriksen flanker [ 36 ] selective attention task during MEG recording. Based on previous literature independently investigating the neural processes supporting visual attention in HAND and ADS pathologies [ 15 , 29 , 31 , 37 ], we predicted that our primary findings would center on parieto-occipital and prefrontal regions, which are strongly activated during selective attention processing. More specifically, we hypothesized that those on the ADS would exhibit stronger neural interference responses than those in the HAND group, and that such differences would occur in the theta range within frontoparietal brain regions.…”
Section: Introductionmentioning
confidence: 99%